PERENCANAAN PENGELOLAAN SAMPAH DI PERUMAHAN TAVANJUKA MAS - Aswadi, Muhammad (MEKTEK, 2011)
The purpose of this research is to know the solid waste volume which produced by society on Tavanjuka MasHousing and to determine the way to ménage solid waste. Collecting data in this research is done byinterview and direct measuring of solid waste volume on Tavanjuka Mas Housing. This research used 65numbers of samples to determine solid waste volume, then it are analyzed with simple linear regression usedMicrosoft Office Excel and geometric method to predict inhabitant sum. From the research result, theaverage solid waste volume produced by society on Tavanjuka Mas Housing1,3599 m3/day, which consist oforganic solid waste 0,920 m3/day and inorganic solid waste 0,4399 m3/day, with organic solid wastepercentage 67,72 % and inorganic solid waste percentage 32,28 %. Solid waste management on TavanjukaMas Housing can be done with sorting way, provision of place and then increasing of facilities like servicetransport of motor wagon with capacity 1 m3 as many 1 unit and the building of while place of exile withcapacity 1m3 for organic solid waste as many 2 units and inorganic solid waste as many 1 unit